Physicochemical Characteristics of Gluten-Free Gyoza Wrappers Made from Rice Flour and Mocaf with the Addition of Kappa Carrageenan - Nur Dyah Bela Putri; Jariyah (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
This study examines the production of gluten-free gyoza wrappers from rice flour and mocaf with the addition of kappa carrageenan. Mocaf has a high amylopectin starch , causing the resulting product to have a sticky texture. Rice flour has a higher amylose than Mocaf, a property that correlates strongly with the ability of gluten-free dough to form a more stable and viscoelastic structure. Kappa carrageenan has the ability to form strong gels through the formation of double helix structures that associate with each other, thereby increasing the viscoelastic properties of food systems. In combination with starch, carrageenan interacts through hydrogen bonds and physical associations, producing a more stable composite gel network that is able to retain water and increase the flexibility and integrity of the dough structure. The purpose of this study was to determine the effect of rice flour and mocaf proportions with the addition of kappa carrageenan on the physicochemical and organoleptic characteristics of gluten-free gyoza wrappers, as well as the best treatment that produces gluten-free gyoza wrappers with organoleptic qualities that are close to or equal to commercial gyoza wrappers. This study used a completely randomized design (CRD) with a factorial pattern and three replicates. The first factor was the proportion of rice flour: mocaf (40:60; 50:50; and 60:40), while the second factor was the addition of kappa carrageenan (8, 10, and 12%). The data were analyzed using ANOVA and DMRT post-hoc test at a 5% confidence level. The best treatment was found in the rice flour: mocaf ratio (40:60) with 8% carrageenan addition, which produced a moisture of 53.72%; ash of 1.67%; starch of 41.97%; amylose of 9.46%; amylopectin of 32.51%; color of 2.56 (same as bone white with R); aroma of 3.04 (same as neutral with R) and texture of 4.04 (slightly more elastic than R).Contribution to Sustainable Development Goals (SDGs):SDG 6: Zero HungerSDG 3: Good Health and Well-being SDG 9: Industry, Innovation and InfrastructureSDG 11: Sustainable Cities and Communities